Endogenous VIP VPAC1 receptor activation modulates hippocampal theta burst induced LTP: transduction pathways and GABAergic mechanisms - Caulino-Rocha, Ana (2022)
© 2022 by the authors. Licensee MDPI, Basel, Switzerland. This article is an open access article distributed under the terms and conditions of the Creative Commons Attribution (CC BY) license (https://creativecommons.org/licenses/by/4.0/).